2015
DOI: 10.1016/j.celrep.2015.06.047
|View full text |Cite
|
Sign up to set email alerts
|

A Floor-Plate Extracellular Protein-Protein Interaction Screen Identifies Draxin as a Secreted Netrin-1 Antagonist

Abstract: Floor-plate-derived extracellular signaling molecules, including canonical axon guidance cues of the Netrin family, control neuronal circuit organization. Despite the importance of the floor plate as an essential signaling center in the developing vertebrate central nervous system, no systematic approach to identify binding partners for floor-plate-expressed cell-surface and secreted proteins has been carried out. Here, we used a high-throughput assay to discover extracellular protein-protein interactions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 44 publications
1
49
1
Order By: Relevance
“…Using AVEXIS [ 6 ] we had previously determined that Vasna is an Islr2 ligand [ 47 ]. By screening an expanded library totaling 194 zebrafish receptor ectodomains [ 17 ], we confirmed the Islr2-Vasna interaction and additionally detected specific binding with its paralog, Vasnb (Fig. 5a ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Using AVEXIS [ 6 ] we had previously determined that Vasna is an Islr2 ligand [ 47 ]. By screening an expanded library totaling 194 zebrafish receptor ectodomains [ 17 ], we confirmed the Islr2-Vasna interaction and additionally detected specific binding with its paralog, Vasnb (Fig. 5a ).…”
Section: Resultsmentioning
confidence: 62%
“…Both Islr2-Vasna and Islr2-Vasnb interactions were detected in both prey/bait orientations, demonstrating the specificity of the observed binding events (Fig. 5a ; [ 17 ]).
Fig.
…”
Section: Resultsmentioning
confidence: 93%
“…A more robust mechanism that has been proposed involves a contact-dependent switch: the contact between a growth cone and its intermediate target could induce a transcriptional change in the neuron and thus result in the insertion of guidance receptors in a precisely timed manner. This has been Gao et al, 2015;Ahmed et al, 2011 Slit (Robo) Plexin A1 identified as alternative Slit receptor Delloye-Bourgeois et al, 2015 Cis binding with RPTP69D turns DsCAM into Slit receptor Alavi et al, 2016…”
Section: Changes In Transcriptionmentioning
confidence: 99%
“…A linker with 19 amino acid residues seems minimally required for separating the functional FN4 and FN5 domains in the context of cell-binding. To verify the difference in netrin-1 adhesion in vitro between the wild-type versions of the human long and short isoforms of DCC, an AVEXIS assay (Bushell et al, 2008 ; Gao et al, 2015 ) was then performed. A fragment of the long isoform of human DCC FN456 was inserted into the AVEXIS prey vector.…”
mentioning
confidence: 99%
“…Scale bar: 20 μm. (B) The in vitro binding of human DCC ectodomains and netrin-1s was examined using an Avexis assay (Bushell et al, 2008 ; Gao et al, 2015 ). Briefly, netrin was biotinylated and attached to a streptavidin plate.…”
mentioning
confidence: 99%